Chromite placer occurrences of the Volga-Ural basin – genesis, sources and industrial potential - A. V. Lalomov; I. R. Rakhimov; A. V. Grigor’eva (Georesursy, 2024)
Chromium is a strategic metal, but more than a half of Russia’s needs are met by imports, so new deposits of chromites, including unconventional placer deposits, are of industrial and scientific interest. Previous studies and current works of the authors of the article have established the chromite placer metal content of Permian-Jurassic deposits of the Volga-Ural basin, which has industrial and potential significance: within the Lukoyanovsky placer area (Nizhny Novgorod region), the industrial chromite content of Jurassic coastal-marine titanium-zirconium placers has been established; in the south-west of Bashkiria, chromite-bearing sands (Sabantuy occurrence) with increased contents, but not yet clear industrial potential. The study of the typomorphism of chromites indicate their close relationship with the chrome spinel of ophiolite associations. The assumed overthrust structure of chromite-bearing hyperbasites of the Urals suggests a wide distribution of chromite-bearing sands within the Upper Permian-Jurassic Volga-Ural paleobasin, in which the increased content of chromites was controlled by hydroand lithodynamic conditions favorable for placer formation. Questions of the genesis of chromite placer occurrences in the Ural part of the East European Platform, their distribution and primary sources need further study.